Mediation in international disputes: a useful tool for peace-making and preventive diplomacy - Hamid, Abdul Ghafur@Khin Maung Sein (Lexis Nexis Malaysia, 2010)
Mediation is one of the oldest and most common conflict resolution mechanisms in international disputes. It has many advantages that make it a very attractive method for dealing with intractable conflicts. When it is applied correctly it can help to manage or settle an interstate or intrastate conflict. Certain attributes of course are necessary for a successful mediation. These include the timing or ripeness of the conflict, the strength and leverage of the mediator, and the effective strategies for implementation and monitoring. Mediation has success stories. Nevertheless, there are a large number of protracted and outstanding conflicts that are still left unsettled. The true spirit of mediation could help them resolved in the near future.